2011
DOI: 10.1088/1674-1056/20/10/100508
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement effect of asymmetry on the thermal conductivity of double-stranded chain systems

Abstract: Enhancement effect of asymmetry on the thermal conductivity of double-stranded chain systems *Zhang Mao-Ping( ) a) , Zhong Wei-Rong( ) a) † , and Ai Bao-Quan( ) b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Various nonlinear models have been proposed to construct a thermal diode theoretically. [10,[14][15][16][17][18][19][20][21][22][23][24] Moreover, benefiting from the boost of nanotechnology, solid thermal diodes have been fabricated in experiments successfully by using specific materials, which paves the way for the practical applications of thermal diode and transistor. [25][26][27][28] These researches revealed that a onedimensional thermal diode model must satisfy two essential conditions: the nonlinear (unharmonic) interaction and asymmetric structure of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Various nonlinear models have been proposed to construct a thermal diode theoretically. [10,[14][15][16][17][18][19][20][21][22][23][24] Moreover, benefiting from the boost of nanotechnology, solid thermal diodes have been fabricated in experiments successfully by using specific materials, which paves the way for the practical applications of thermal diode and transistor. [25][26][27][28] These researches revealed that a onedimensional thermal diode model must satisfy two essential conditions: the nonlinear (unharmonic) interaction and asymmetric structure of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, MD simulation has been a useful method to study thermal conductivity by phonons. [7][8][9][10][11][12][13][14][15][16][17][18][19] The anisotropy of thermal conductivity, [15] interface effect, [9,16] and size effect [7,10,11] on thermal conductivity were specially discussed. In MD simulations, the thermal conductivity can be computed either using equilibrium MD (EMD) [13,16,20,21] or non-equilibrium MD (NEMD).…”
Section: Introductionmentioning
confidence: 99%
“…In MD simulations, the thermal conductivity can be computed either using equilibrium MD (EMD) [13,16,20,21] or non-equilibrium MD (NEMD). [7,[9][10][11]14,[16][17][18][19] Relatively, the NEMD method provides direct information about transport phenomenon. [7,22] So in this paper, the phonon conductivity of alpha-zirconium is theoretically estimated using the NEMD method.…”
Section: Introductionmentioning
confidence: 99%